Employment Law Politics in Indonesia - Dr. Jasni bin Sulong; Muhamad Ramzy Fernanda (AT-TAFAHUM: Journal of Law, 2024)
Employment law policy in Indonesia reflects the government's efforts to balance worker protection with the demands of national economic development. The enactment of Law No. 11 of 2020, subsequently reinforced by Law No. 6 of 2023 concerning Job Creation, has significantly transformed Indonesia's employment legal framework by promoting labor market flexibility while raising concerns regarding the protection of workers' rights. This study aims to analyze the direction of Indonesia's employment law policy, examine the evolution of labor regulations, and evaluate the implementation of legal protection for workers amid contemporary economic and technological developments. The research employs a normative legal method using statutory, conceptual, and analytical approaches. Data were collected through a comprehensive review of primary, secondary, and tertiary legal materials and analyzed qualitatively. The findings indicate that although Indonesia has established a comprehensive legal framework governing employment relationships, labor protection, and industrial dispute resolution, significant challenges remain in its implementation. Amendments introduced through the Job Creation Law have increased flexibility in fixed-term employment agreements and outsourcing, enhancing business competitiveness but also creating greater job insecurity. Furthermore, the rapid expansion of the digital economy and platform-based employment has exposed regulatory gaps, leaving many gig workers without adequate legal protection. Weak law enforcement, limited government supervision, and the unequal bargaining position of workers further undermine the effectiveness of existing regulations. Therefore, Indonesia's employment law policy should be strengthened through more adaptive legislation, effective enforcement mechanisms, and balanced legal reforms that simultaneously promote investment, legal certainty, and the protection of workers' rights.